Pengendalian Defect Visual dengan Pendekatan Statistical Quality Control sebagai Upaya Perbaikan Produk - Zukhruf, Friska Putri; Nugraha, Asep Erik; Nugraha, Billy (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2023)
PT. XYZ is a B2B plastic packaging producing industry, in bottle products there are 3 criteria for visual defects that occur, namely black spots, flashing, and codensation. The purpose of this study is to analyze the quality control of visual defects that occur and improvements that must be made. In this study, the Statistical Quality Control method is used, the tools used in this study are U-control chart. In addition, additional tools such as pareto diagrams and fishbone diagrams are used to analyze improvements that can be made. From the results of the research conducted, it is known that quality control at PT. XYZ is still within the control limits, then an improvement analysis is carried out using the 5W + 1H method to determine the actions that can be taken in order to minimize visual defects that can occur.